"Hello are you available?" Dealing with online frauds and the role of forensic science. (June 2020) - Ribaux, Olivier; Souvignet, Thomas R.
Abstract: On August 6, 2019, the 119 members of the School of criminal justice, forensic science and criminology at the University of Lausanne were the target of an online scammer. His/her modus operandi consisted of email masquerading as the Director of the School in an attempt to induce the victims to buy digital gift cards and to transmit the card usage code to the perpetrator. The first author of this paper is the Director of the School, and the second is an expert in digital forensic science and a professor of the School. They worked together in real time to deal with the fraud. Because the fraud occurred in a School of forensic science and criminology, it raised many questions on a variety of overlapping dimensions. The objective of this study was, therefore, to draw lessons from this case from several perspectives ranging from forensic science to cybersecurity, and from practical to academic. The response to the incident has been treated in four typical distinguishable phases: (1) fraud detection; (2) crisis management; (3) post-incident analysis; and (4) reporting to different communities. We conclude this paper by taking lessons from the case to express the essential role of forensic knowledge and crime analysis in interpreting the information conveyed by digital traces to develop innovative cross-disciplinary models for preventing, detecting, analysing, investigating and responding to online fraud. Highlights: A case study for deciphering the anatomy of a specific online fraud targeting a University Department. Reasons of the extent of these frauds, their pervasiveness and the difficulties institutions have in containing them. A concrete situation illustrating the value of extending DFIR methodologies in an interdisciplinary manner. Crime analysis, forensic science or traceology are pivotal, but generally not considered as such.